APLIKASI SISTEM PENJUALAN SPAREPART HANDPHONE DI CV. AUTO CELL BERBASIS WEB - Masum Masum; Huswatun Hasanah; Saepullah Saepullah (LPPM Unbaja, 2023)
The purpose of this research is to make it easier to access data and prepare reports needed by those who need it. The method used in this research is the waterfall model which begins with research on the running system, designing, coding, and maintaining the sales system so that sales information and sales report preparation can run quickly, precisely and accurately. The results obtained are regarding sales applications integrated with databases to easily, quickly, and accurately support the sales process. The conclusion that can be drawn from this application is that the management of sales reports can be well documented because it is equipped with a database, storage has become one unit, can reduce redundancies or data duplication, can display the required sales information so that it can make it easier for officers to make sales reports.